Researching Parental Socialization Styles across Three Cultural Contexts: Scale ESPA29 Bi-Dimensional Validity in Spain, Portugal, and Brazil - Martínez, Isabel (2019)
Recent research that relates parenting with adolescent adjustment has shown the importance of considering the cultural context of the relationship. New results are emerging when considering the classical four-typologies model of parental socialization in some European and South-American countries. Among the instruments used in this emergent research is the Parental Socialization Scale ESPA29. This scale is a bi-dimensional parenting instrument that was specifically developed to measure the four parenting typologies, through the dimensions of acceptance/involvement and strictness/imposition. This study examines the good fit of the orthogonal bi-factor model based on the ESPA29 versus one-dimensional and bi-dimensional oblique alternative models, with three adolescent samples from 12 to 17 years old (53.4% girls), from Spain (N = 826), Portugal (N = 752), and Brazil (N = 628). We applied structural equation models (SEMs) to analyze the fit of the models to the data. The results confirm a better fit to the data for the orthogonal bi-factor model versus one-dimensional and bi-dimensional oblique alternative models across country, adolescent sex, and the three age groups. Additionally, the convergent validity of the scale was proved by showing the relation of the two parenting dimensions with self-concept. The results guarantee the adequacy of the ESPA29 to measure parenting styles.